Simulation and Gaming - Cvetković, Dragan (IntechOpen, 2018)
The book "Simulation and Gaming" discusses the following topics and research areas: game-based methods of problem solution and data processing, analysis, and information mining; educational games and game features, including game characteristics, story, mechanics, and methodology; development of integrated games tasked with helping students in interpreting, translating, and manipulating the field of kinematics through formal presentations; possibility of research integration through real and practical examples and games as well, in the field of physics; analysis of game engines from various aspects such as modularity, performance, and usability; virtual reality (VR) and interaction mechanisms used for three-dimensional (3D) game development; analysis, development, design, implementation, and evaluation of the simulation model in the field of engineering and metallurgy, according to ADDIE model; concept of computational thinking, with an accent on its inclusion in compulsory education; overview of the current prominence of AI simulation based in the gaming leisure industry, mainly for research purposes in the context of gambling and forecasting of online casino patron's churn behavior; innovative modeling and simulation approach using newly proposed advanced game-based mathematical framework, unified game-based acquisition framework, and a set of war-gaming engines to address the challenges for acquisition of future space systems; modification of simulation of a complex system and a physics model through programming, achieved with a block-based programming language.